Advances in Targeted Therapies for Non-Small Cell Lung Cancer: Current Trends and Challenges - Akhter Ali Khan, Qasim Nawaz, Fazal Ghani, Samid Ur Rehman, Burhanullah, Zia Ur Rehman (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To evaluate the efficacy of targeted therapies in Non-Small Cell Lung Cancer (NSCLC) patients, specifically focusing on the impact of molecular alterations on progression-free survival (PFS) and overall survival (OS). Methodology: The study was from June 2022 to June 2023, involving 200 NSCLC patients. Patients were grouped based on the presence or absence of actionable mutations, including EGFR, ALK, ROS1, KRAS, and BRAF. A retrospective analysis was conducted, evaluating patient demographics, treatment responses, and survival data. Results: The results indicated that patients with actionable mutations had significantly better outcomes compared to those without mutations. The mean PFS for patients with actionable mutations was 14.5 months, while patients without mutations had a mean PFS of 7.3 months (p-value = 0.001). Similarly, the mean OS for patients with actionable mutations was 21.6 months, compared to 15.9 months for patients without mutations (p-value = 0.002). Treatment responses showed that 48% of patients had partial responses, 25% had stable disease, 17% had complete responses, and 10% experienced progressive disease. Conclusion: This study supports the importance of molecular profiling in guiding targeted therapies for NSCLC patients. Personalized treatment strategies based on molecular alterations significantly improve survival outcomes. Future studies should focus on overcoming resistance mechanisms and exploring combination therapies to further improve treatment efficacy. Keywords: NSCLC, targeted therapies, molecular alterations, survival, progression-free survival.